Employing Land-Based Anti-Ship Missiles in the Western Pacific - Kelly, Terrence K. (RAND Corporation, 2013)
Land-based anti-ship missiles (ASMs) feature prominently in the capabilities of many island nations in the Western Pacific, but the United States currently lacks such systems. This report illustrates the potential strategic advantages of the United States working with partners to build a coalition ASM capability, particularly in the event of a conflict with China, and includes an assessment of logistical challenges and positioning approaches.